Peril on the page - Loudon, Margaret (Loudon, Margaret. Open book mysteries, 2022)
Penelope Parish is ready to close the book on her amateur sleuthing--from now on, The Open Book's writer-in-residence will be sticking to villains of the fictional variety while she puts the final touches on her new novel. But when an author is murdered inside the bookshop, all of Upper Chumley-on-Stoke goes on high alert. Now it's up to Pen and the quirky citizens of Chumley to stop a killer and protect the charming British town she's begun to call home.